Current scenario and future perspectives of postgraduate medical education in India - Abhijat Sheth (Apollo Medicine)
Currently, India is lagging behind in the medical doctors-to-population ratio, and the problem is even critical for postgraduate (PG)-qualified specialist doctors. However, there are rapidly advancing measures that are being taken toward improving health care for the whole population. The Government has the mandate to increase the number of seats for PG medical education and the teaching faculty to address the shortage of specialized medical doctors. The future of the PG medical education curriculum would include enhancements such as broader use of technology and inclusion of courses such as medical ethics and health economics. In addition, incorporating virtual learning, flipped classroom models, simulation studies, and interprofessional education in PG medical education would help to improve the quality and efficiency of medical education. Integration, innovations, and implementation are crucial keys to the reforms and should help PG medical education to achieve new heights in India in the near future.